Kajian Motivasi Kerja Dan Budaya Organisasi Terhadap Kepuasan Kerja serta Dampaknya Pada Kinerja Pegawai BMKG Stasiun Klimatologi Malang - Wahyudi, Imam (Fakultas Ekonomi Universitas Wisnuwardhana, 2019)
Abstract. The purpose of this study was to determine the effect of workmotivation, organizational culture on employee performance through jobsatisfaction. type of research is explanatory research, data collectiontechniques are questionnaires. the sample in this study amounted to 37respondents with the sampling technique was census/population sampling,the scale of measurement using a Likert scale. Quantitative analysis usesvalidity test, reliability test, classic assumption and path analysis. Basedon the results of this study indicate that work motivation (X1) andorganizational culture (X2) have a significant effect on performance (Y2)through job satisfaction (Y1). The results of path analysis show the directeffect of work motivation and organizational culture on employeeperformance greater than indirect effects through job satisfaction.Keywords: work motivation, organizational culture, job satisfaction andperformance